Thoracoabdominal Approach for Large Retroperitoneal Masses: Case Series and Review. (10th March 2019) - Venkat, Siv; Matteliano, Andre; Drachenberg, Darrel
Abstract : The thoracoabdominal incision was first described in 1946 as an approach to concomitant abdominal, retroperitoneal, and thoracic injuries. In urology, this technique was popularized in 1949 for the resection of large renal tumours. Today, it is reserved for complex cases where optimal exposure of the renal hilum and adrenal and superior pole of the kidney is necessary. We present four consecutive cases in which this approach was taken by a single surgeon at our tertiary surgical centre. The outcomes, postoperative course, and pathology are described. We provide a comprehensive literature review and outline the indications, advantages, and disadvantages of this approach. Objectives. To present a case series outlining the efficacy and safety of the thoracoabdominal incision in complex oncologic procedures in urology. Methods. Four cases utilizing the thoracoabdominal incision, performed by a single surgeon at our tertiary care center, were reviewed. Case history, preoperative imaging, intraoperative experience, postoperative course, final pathology, and complications were examined. A thorough literature review was performed and comparison made with historical cohorts for estimated blood loss, length of stay, and complications encountered versus other common surgical approaches. The indications, advantages, and disadvantages of the thoracoabdominal approach were outlined. Results. All patients had large retroperitoneal masses of varying complexity, requiring maximal surgical exposure. Surgery was straightforward in all cases, without any significant perioperative or postoperative complications. Postoperative pain, length of hospital stay, estimated blood loss, and analgesia requirements were all similar to open and mini-flank approaches in review of historical case series cohorts. Laparoscopic approaches had lower estimated blood loss and length of stay. Conclusions. The thoracoabdominal approach is rarely utilized in urological surgery, due to the perceived morbidity in violating the thoracic cavity. These cases outline the benefit of the thoracoabdominal approach in select cases requiring maximal surgical exposure, and the generally benign postoperative course that appropriately selected patients may hope to endure. Postoperative pain, length of hospital stay, estimated blood loss, and analgesia requirements can be expected to be similar open and mini-flank approaches. As expected, laparoscopic approaches had lower estimated blood loss and length of stay.